Educational Research Methodology in Practice: “Unravelling the Secrets of Successful Research Project” - Feussi, Dr. Polycarpe; Mbohwa, Prof. Charles; Madonsela, Dr. Nelson Sizwe; Edoun, Dr. Emmanuel Innocents (Educational Research Methodology in Practice: “Unravelling the Secrets of Successful Research Project”, 2024)
"Unravelling the Secrets of Successful Research Projects" is a comprehensive guide to educational research methodology. It provides practical insights and strategies for effective education research. This resource equips readers with the essential tools and knowledge needed to navigate research projects. Researchers can confidently embark on their scholarly journey, producing high-quality educational research endeavors. With practical examples, case studies, and step-by-step instructions, this guide delves into every aspect of the research process. It provides guidance on selecting research methods, designing studies, and addressing ethical considerations. This book includes chapters on emerging trends and techniques in educational research. The authors offer advice on overcoming common challenges in the research process. With an engaging writing style and accessible approach, this book makes complex concepts and methodologies understandable. Whether you are a graduate student or an experienced researcher, this expanded edition is an essential companion for educational research endeavors. By expanding the boundaries of educational research, this book contributes to a better understanding of education and drives meaningful change and progress in the field.